Advancing integrated research on European river–sea systems: the DANUBIUS-RI project. Issue 6 (2nd November 2018) - Bradley, C.; Bowes, M. J.; Brils, J.; Friedrich, J.; Gault, J.; Groom, S.; Hein, T.; Heininger, P.; Michalopoulos, P.; Panin, N.; Schultz, M.; Stanica, A.; et al.
ABSTRACT: Research at the interface between terrestrial, riverine, estuarine and marine environments is frequently constrained by significant disciplinary and geographical boundaries. This article outlines an international initiative, DANUBIUS-RI, which aims to address these problems by facilitating biogeochemical monitoring and interdisciplinary research on river–sea systems. The scope of the project spans the environmental, social and economic sciences and was accepted into the European Strategy Forum on Research Infrastructures roadmap in 2016. When operational, DANUBIUS-RI will offer researchers access to interdisciplinary expertise, facilities and European river–sea systems, providing a comprehensive platform for multidisciplinary research and training.